Effects Of Thermal Annealing Of Pt Schottky Contacts On n-GaN. - C, W Chin; Hassan, Z; F, K Yam (2007)

(untitled)
In this paper, the Schottky behavior of Pt contact on n- GaN grown by RF-plasma assisted molecular beam epitaxy was investigated under different annealing temperatures.